2008
DOI: 10.1111/j.1440-172x.2008.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Near misses: Paradoxical realities in everyday clinical practice

Abstract: This qualitative study was conducted to define and describe what constitutes and contributes to near miss occurrences in the health-care system and what is needed to ensure safer processes of care. Nine health-care organizations (13 sites total) including six academic health sciences centres (acute care, mental health and geriatric) and three community hospitals participated in this study. The final sample consisted of 37 focus groups (86 in the nursing staff only; 62 in the pharmacy staff only; and 99 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Jeffs et al . ). Other studies further identified analysing, counselling, educating, informing and clinical nursing skills as the important antecedents to patient advocacy, whereas this study provides authentic examples of how nurses integrate the crucial elements of proactiveness and vigilance to contribute to patient safety in real clinical contexts (Negarandeh et al .…”
Section: Discussionmentioning
confidence: 97%
“…Jeffs et al . ). Other studies further identified analysing, counselling, educating, informing and clinical nursing skills as the important antecedents to patient advocacy, whereas this study provides authentic examples of how nurses integrate the crucial elements of proactiveness and vigilance to contribute to patient safety in real clinical contexts (Negarandeh et al .…”
Section: Discussionmentioning
confidence: 97%
“…A need for a patient-centred practice has been always emphasised in order to ensure providing safe care (Jeffs et al, 2008). Nurses are expected to provide information to patients when it is deemed to be appropriate (Brataas et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This adds to a relatively small, but growing, knowledge base on near misses as recovery processes in healthcare. 4,[9][10][11][12] Given the serious complications associated with pressure ulcers, 8 future implications include continued investment in developing and evaluating systematic and educational approaches that enhance nurses' ability to assess for, recognize patterns in, and implement evidenceinformed care processes associated with pressure ulcers. This investment will ensure that nurses can apply existing and evolving knowledge to minimize the risk for and enhance the healing processes of pressure ulcers.…”
Section: Implications For Nursingmentioning
confidence: 99%
“…Moreover, those strategies are primarily enacted by nurses, as part of their surveillance role of practice; nurses detect potential complications and subsequently prevent adverse patient outcomes from pressure ulcers. 4,5,8 Although there is growing evidence on the role of nursing in near misses [9][10][11][12] and error recovery, 4 no studies were found that explored the surveillance of pressure ulcers as a near-miss process. Insight gained from such an inquiry is posited to add to both (1) the evolving patient safety science knowledge base on near misses as recovery processes and (2) the surveillance role of nurses in detecting and minimizing risk and error.…”
mentioning
confidence: 99%